The Notion of Homeland, “Imaginary Homeland” and Wounded Memory in Khaled Hosseini’s The Kite Runner - Sulaiman, Suraiya (School of Social Sciences, 2015)
This article explores the idea of homeland, “imaginary homeland” and wounded memory in Khaled Hosseini’s debut novel, The Kite Runner (2003). The idea of homeland, which includes the illustration of a person’s nostalgia towards homeland, is a significant topic of discussion among scholars of diaspora studies. The article demonstrates that Afghanistan as depicted in Hosseini’s novel represents the author’s nostagic feeling towards his home country. The novel also illustrates the ideas of a shattered dream and fragmented memories of diaspora subjects which are caused by the loss of homeland as discussed in Salman Rushdie (2006)’s seminal article, “Imaginary